Colonization by ceftazidime/avibactam-resistant KPC-producing Klebsiella pneumoniae following therapy in critically ill patients. (May 2023) - Gaibani, Paolo; Bovo, Federica; Bussini, Linda; Bartoletti, Michele; Lazzarotto, Tiziana; Viale, Pierluigi; Pea, Federico; Ambretti, Simone
Abstract: Objectives: Ceftazidime-avibactam (CAZ-AVI)–based treatments have been associated with the emergence of resistance in KPC-producing Klebsiella pneumoniae (KPC-Kp) isolates after antimicrobial exposure. Here, we evaluated the CAZ-AVI resistance development in KPC-Kp isolated from patients treated with CAZ-AVI–based therapy. Methods: We enrolled adult patients treated with CAZ-AVI–based regimens between January 2020 and January 2021. Carbapenemase-producing isolates collected from clinical samples and rectal swabs were evaluated for CAZ-AVI resistance development after antimicrobial exposure. KPC-Kp developing CAZ-AVI resistance and parental susceptible strains were genomically characterized. Whole genome sequencing was performed by using the Illumina iSeq100 platform and genomes were analyzed for antimicrobial-resistance genes, plasmid and porins sequences. Results: We enrolled 90 patients treated with CAZ-AVI–based therapy and 62.2% (56/90) of them were colonized by KPC-producers before CAZ-AVI–based treatment and 6.6% acquired colonization during therapy. Six (6.6%) patients developed infections because of resistant KPC-Kp after CAZ-AVI exposure and 3 (3.3%) of them developed CAZ-AVI resistance in the rectum. Development of resistance among KPC in the rectum occurred after 32 (IQR, 9–35) days of therapy and after 30 (IQR, 22–40) days in clinical specimens. Genetic analysis demonstrated that the development of CAZ-AVI resistance was associated with mutated bla KPC-3 ( bla KPC-31, bla KPC-53, bla KPC-89, and bla KPC-130 ) and phylogenetic analysis demonstrated a close genomic relationship between KCP-Kp collected from rectum and clinical samples of the same patient. Discussion: Antimicrobial exposure induce a higher incidence of CAZ-AVI resistance development in the blood and respiratory tract than in the rectum (6.7% vs. 3.3%) of CAZ-AVI–treated patients and genome analysis showed that resistance was associated with mutated bla KPC-3 variants.